EVALUASI PENGENDALIAN PELAKSANAAN DAN PENJADWALAN PROYEK PERPIPAAN DI KOTA MALANG - Adiman Fariyadin, M. Ruslin Anwar, Indradi Wijatmiko (Prokons: Jurnal Teknik Sipil, 2016)
The construction project is a series of activities carried out only one time and is generally short-term. In a series of activities, there is a process that is processing the project resources becoming an activity results in the form of the building. The process that occurs in a series of these activities would involve related parties, either directly or indirectly. The definition of project management according to Ervianto (2005) is all the planning, execution, control and coordination of a project from the beginning (the idea) to berakhirya project to ensure the timely implementation of the project, right cost and right quality. The results of the analysis of cost control, time and resources on a pipeline project Malang using Earned Value indicates delays in the work on the planned time, but the cost is still below the budgeted costs or in other words, the project did not suffer losses, the project can be completed by the time work 20 weeks or later 42 days from the planned time and 12 days later than the time of realization. While the lower cost Rp. 398,159,830 of the budgeted costs. The results of the project's working time scheduling with Repetitive scheduling method that the project can be completed on day 62 or 16 days sooner than the planned time.Keywords: Repetitive scheduling Method, Evaluation Control, Scheduling, Earned Value